Study of Complementary Feeding and Children’s Nutritional Status in Jambi City - Perdana, Silvia Mawarti; Butar, Marta Butar; Syah, Muhammad Nur Hasan (Ikatan Sarjana Gizi Indonesia (ISAGI), 2024)
Providing adequate complementary feeding, quantitatively and qualitatively, supports children’s nutritional status. This study aims to analyze complementary feeding and children’s nutritional status in Jambi City. This type of research is quantitative with a cross-sectional study design conducted in 2023. The population used in this research was children aged 6-24 months in Jambi City with 116 respondents as sample taken using accidental sampling technique. Primary data collection was carried out through validated questionnaires, 1x24 hour food recall forms, and food frequency questionnaires. Data processing was carried out univariately and bivariately to see the correlation between complementary feeding and nutritional status which was tested using spearman correlation test. Nutritional status data shows that 6.9% of children are underweight and 13.8% of children are at risk of being overweight; as many as 24.1% of children were severely stunted and 15.5% were stunted; and as many as 53.4% ​​of children experience problems of under- and over-nutrition. As many as 62% of children at the age of 6 months have the first food/drinks given consisting of: formula milk, rice porridge/tim rice/rice/mashed side dishes, and mashed fruit with mashed texture/thick porridge fed by parent or caregiver. The average nutrition intake obtained by children from complementary feeding is 889 kcal energy (90.2 %) and 34.3 g protein (201.1 %). There is no significant correlation between complementary feeding and nutritional status of children because this study has not followed the continuous complementary feeding. Complementary feeding for children needs controlling of daily nutrition intake by parents.